Production of ?-amylase in semi solid substrate fermentation by Bacillus amyloliquefaciens - Yaras, Ali; Selen, Veyis; Ozer, Dursun (Elsevier Sci Ltd, 2011)
[Abstract Not Available]
European Biotechnology Congress -- SEP 28-OCT 01, 2011 -- Istanbul, TURKEY